2020
DOI: 10.1108/bl-08-2020-0057
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of artificial intelligence integrated CRM system: an empirical study of Indian organizations

Abstract: Purpose The purpose of this study is to explore the behavioral intention of the employees to adopt artificial intelligence (AI) integrated customer relationship management (CRM) system in Indian organizations. Design/methodology/approach To identify the factors impacting the behavioral intention of the employees to adopt AI integrated CRM system in Indian organizations helps of literature review and theories have been taken. Thereafter, some hypotheses have been formulated followed by the development of a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 67 publications
2
36
0
Order By: Relevance
“…Perceived usefulness and perceived ease of use have been reported as autonomous factors but with less dependence power and less driving power, and they occupy the same level and are interconnected (Moslehpour et al , 2018; Rahmi et al , 2018). Leadership support, reported to be at the most basic level in the ISM model, is the most important variable in considering the adoption of AI in Indian management institutes, as also reported by Chatterjee et al (2020) and Keengwe et al (2009) in the new technology adoption.…”
Section: Resultsmentioning
confidence: 87%
“…Perceived usefulness and perceived ease of use have been reported as autonomous factors but with less dependence power and less driving power, and they occupy the same level and are interconnected (Moslehpour et al , 2018; Rahmi et al , 2018). Leadership support, reported to be at the most basic level in the ISM model, is the most important variable in considering the adoption of AI in Indian management institutes, as also reported by Chatterjee et al (2020) and Keengwe et al (2009) in the new technology adoption.…”
Section: Resultsmentioning
confidence: 87%
“…The different interpretations of IC lead to the conclusion that IC includes abilities and resources that are valuable, rare, inimitable and non-substitutable. If a firm can achieve this, it can ensure better performance along with sustainable CA (Zlatkovic, 2018;Bhattacharjee et al, 2020;Chatterjee, 2020;Ghosh et al, 2020). Different scholars have classified IC with different dimensions such as SC and HC (Edvinsson and Malone, 1997;Christos, 2019;Chaudhuri et al, 2021;Majumdar et al, 2020;Bhattacharjee et al, 2020;Chatterjee et al, 2021b); SC, employee capital and consumer capital (Zerenler et al, 2008;Barrena-Mart ınez et al, 2019;Chatterjee et al, 2021a); and social capital, HC and organization capital (Reed et al, 2006;McDowell et al, 2018;Chatterjee et al, 2020).…”
Section: Research Contextmentioning
confidence: 99%
“…If a firm can achieve this, it can ensure better performance along with sustainable CA (Zlatkovic, 2018;Bhattacharjee et al, 2020;Chatterjee, 2020;Ghosh et al, 2020). Different scholars have classified IC with different dimensions such as SC and HC (Edvinsson and Malone, 1997;Christos, 2019;Chaudhuri et al, 2021;Majumdar et al, 2020;Bhattacharjee et al, 2020;Chatterjee et al, 2021b); SC, employee capital and consumer capital (Zerenler et al, 2008;Barrena-Mart ınez et al, 2019;Chatterjee et al, 2021a); and social capital, HC and organization capital (Reed et al, 2006;McDowell et al, 2018;Chatterjee et al, 2020). Studies have revealed that most acceptable dimensions of IC consist of HC, SC and CC (Bontis, 1999;Zerenler et al, 2008;Sumedrea, 2013;Secundo et al, 2018;Vrontis et al, 2019;Glykeria, 2019).…”
Section: Research Contextmentioning
confidence: 99%
“…Family firms can extract the best potential from technological advancements by using the opportunities (Gurbaxani and Dunkle, 2019;Zahra et al, 2005). Family firms need to recognize the technological opportunities to use the updated innovations that would help them to accurately analyze customers' data at less cost with modern technology such as artificial intelligence (AI), blockchain and internet of things (Chatterjee et al, 2019(Chatterjee et al, , 2020a. In this digital era, family firms will not be able to sustain completeness and survive if they continue with their existing business model.…”
Section: Perceived Technological Opportunitiesmentioning
confidence: 99%
“…In this age of digital economy, family firms must focus on digital transformation and digital innovation for their survival (Nambisan, 2017;Chatterjee et al, 2019). They need to use technology like AI-integrated customer relationship management systems (Chatterjee et al, 2020a) to know their customers better and quicker, incurring less cost (Leong et al, 2016). Family firms should use the latest technology platform to keep pace with other firms, shaking off their age-old idea of favoring stability over change (Canterino et al, 2013).…”
Section: Moderating Role Of Strategic Planning and Adoption Of Techno...mentioning
confidence: 99%